MEWUJUDKAN PENGEMBANGAN MASYARAKAT MELALUI OPTIMALISASI PENGOLAHAN, PENGEMASAN, DAN PEMASARAN KOPI DI DESA PAKEL KECAMATAN LICIN BANYUWANGI - Jon Iskandar Bahari (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
The development of agricultural business today is growing rapidly especially for coffee farmers whereas coffee is in demand as one of the efforts of farmers who are worthy to be developed or marketed because it has a potential business prospects. So the coffee farmer business became the main source of income and investment in Pakel village especially Krajan Hamlet. Coffee farmers are very helpful in raising the income and living standards of the people of Krajan village. The coffee farmer business has long known society. In recent years, coffee business is increasing in population, it is seen from the number of people who choose to plant coffee trees. So that there is very strict competition in the company, each company offers competitive prices, quality products, satisfactory service, then in the management of coffee farmers are required to be more innovative in processing, packing , market their products to the superior. It is necessary for coffee farmers to compete in the free market. The results of the observation of Community empowerment Learning in Pakel Village can be concluded that it is necessary to increase the processing, packaging and marketing of coffee because there are still many people selling coffee at a low price. The training was held by KKN students as well as lecturers attended by coffee farmers, PKK mothers, as well as representatives from BUMDes.